2017
DOI: 10.1177/1012690216687979
|View full text |Cite
|
Sign up to set email alerts
|

Respect? An investigation into the experience of referees in association football

Abstract: This article focuses on the response by 2,056 football referees across all 51 County Football Associations in England, the Isle of Man, Jersey and Guernsey to an online survey conducted from 30 September 2015 to 30 November 2015 regarding their experience of officiating since the implementation of a Respect programme in 2008 by the English Football Association. In assessing the impact of the programme, whilst 54 per cent of referees felt that it has been somewhat successful, there remains a need to implement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
5
25
0
Order By: Relevance
“…The Respect Program began by initially identifying grassroots or mass participation football as the setting for change, utilising online videos, codes of conduct and barriers for parents and spectators to remain behind during matches. The program adopted the characteristics of a public information campaign, aimed at a large targeted population, aspiring to alter behaviour through the dissemination of knowledge to the targeted population, in this case players, coaches, spectators and parents (Cleland, O'Gorman & Webb, 2017). The overarching aim of the Respect Program is to increase the recruitment and retention of referees, and to achieve improved behavior towards match officials (Cleland, O'Gorman, & Bond 2015).…”
Section: The Respect Programmentioning
confidence: 99%
“…The Respect Program began by initially identifying grassroots or mass participation football as the setting for change, utilising online videos, codes of conduct and barriers for parents and spectators to remain behind during matches. The program adopted the characteristics of a public information campaign, aimed at a large targeted population, aspiring to alter behaviour through the dissemination of knowledge to the targeted population, in this case players, coaches, spectators and parents (Cleland, O'Gorman & Webb, 2017). The overarching aim of the Respect Program is to increase the recruitment and retention of referees, and to achieve improved behavior towards match officials (Cleland, O'Gorman, & Bond 2015).…”
Section: The Respect Programmentioning
confidence: 99%
“…In one study, all premier league referees surveyed reported being subjected to violent or abusive behaviour as a consequence of officiating [38]. The negative opinions of referees displayed by players and spectators [39] have persisted despite campaigns intended to promote respect [40,41]. Though referees at all levels of competition may be subject to abuse, conflict experienced by referees at the higher levels is more likely to viewed by a large audience (e.g., larger crowds and televised), potentially leading to confrontation outside the match, wider ridicule, and a perceived loss of social status.…”
Section: Discussionmentioning
confidence: 99%
“…In organised contests, referees function as 'interpreters and enforcers of the conditions' as 'guardians of the spirit of the game' and enforcers of explicit rules, 'the traditions and customs of the sport, the unwritten rules' and 'enforcers of equality' preserving the order of the competition and the game as such (Clifford and Feezell 2010, 62). Despite this complex task, referees and refereeing is an under-explored field of research (Nutt 2007), especially the experiences of referees in youth soccer (Cleland, O'Gorman, and Bond 2015;Cleland, O'Gorman, and Webb 2018). Previous research has explored different influencing variables on refereeing, such as crowd noise, threat and aggression, factors influencing referees to leave the game altogether, policy implementation, social pressure and referees' interpretations and use of rules (Folkesson et al 2002;Friman, Nyberg, and Norlander 2004;Di Corrado, Pellarin, and Agostini 2011;Praschinger, Pomikal, and Stieger 2011;Cleland, O'Gorman, and Bond 2015;Cleland, O'Gorman, and Webb 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this complex task, referees and refereeing is an under-explored field of research (Nutt 2007), especially the experiences of referees in youth soccer (Cleland, O'Gorman, and Bond 2015;Cleland, O'Gorman, and Webb 2018). Previous research has explored different influencing variables on refereeing, such as crowd noise, threat and aggression, factors influencing referees to leave the game altogether, policy implementation, social pressure and referees' interpretations and use of rules (Folkesson et al 2002;Friman, Nyberg, and Norlander 2004;Di Corrado, Pellarin, and Agostini 2011;Praschinger, Pomikal, and Stieger 2011;Cleland, O'Gorman, and Bond 2015;Cleland, O'Gorman, and Webb 2018). The stress factors of refereeing have been identified as a fear of failure, limited time for decision making, verbal aggression and pressure from players, coaches and the crowd (Di Corrado, Pellarin, and Agostini 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation